In Vivo Assessment of Neuroinflammation in 4‐Repeat Tauopathies. Issue 4 (27th November 2020) - Palleis, Carla; Sauerbeck, Julia; Beyer, Leonie; Harris, Stefanie; Schmitt, Julia; Morenas‐Rodriguez, Estrella; Finze, Anika; Nitschmann, Alexander; Ruch‐Rubinstein, Francois; Eckenweber, Florian; Biechele, Gloria; Blume, Tanja; et al.
ABSTRACT: Background: Neuroinflammation has received growing interest as a therapeutic target in neurodegenerative disorders, including 4‐repeat tauopathies. Objectives: The aim of this cross‐sectional study was to investigate 18 kDa translocator protein positron emission tomography (PET) as a biomarker for microglial activation in the 4‐repeat tauopathies corticobasal degeneration and progressive supranuclear palsy. Methods: Specific binding of the 18 kDa translocator protein tracer 18 F‐GE‐180 was determined by serial PET during pharmacological depletion of microglia in a 4‐repeat tau mouse model. The 18 kDa translocator protein PET was performed in 30 patients with corticobasal syndrome (68 ± 9 years, 16 women) and 14 patients with progressive supranuclear palsy (69 ± 9 years, 8 women), and 13 control subjects (70 ± 7 years, 7 women). Group comparisons and associations with parameters of disease progression were assessed by region‐based and voxel‐wise analyses. Results: Tracer binding was significantly reduced after pharmacological depletion of microglia in 4‐repeat tau mice. Elevated 18 kDa translocator protein labeling was observed in the subcortical brain areas of patients with corticobasal syndrome and progressive supranuclear palsy when compared with controls and was most pronounced in the globus pallidus internus, whereas only patients with corticobasal syndrome showed additionally elevated tracer binding in motor and supplemental motor areas. The 18 kDa translocator protein labeling was not correlated with parameters of disease progression in corticobasal syndrome and progressive supranuclear palsy but allowed sensitive detection in patients with 4‐repeat tauopathies by a multiregion classifier. Conclusions: Our data indicate that 18 F‐GE‐180 PET detects microglial activation in the brain of patients with 4‐repeat tauopathy, fitting to predilection sites of the phenotype. The 18 kDa translocator protein PET has a potential for monitoring neuroinflammation in 4‐repeat tauopathies. © 2020 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society